2011
DOI: 10.3324/haematol.2011.047035
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction of red blood cell transfusion requirements by changing from a double-unit to a single-unit transfusion policy in patients receiving intensive chemotherapy or stem cell transplantation

Abstract: BackgroundTraditionally, single-unit red blood cell transfusions were believed to be insufficient to treat anemia, but recent data suggest that they may lead to a safe reduction of transfusion requirements. We tested this hypothesis by changing from a double-to a single-unit red blood cell transfusion policy. Design and MethodsWe performed a retrospective cohort study in patients with hematologic malignancies receiving intensive chemotherapy or hematopoietic stem cell transplantation. The major end-points were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 36 publications
5
90
1
2
Order By: Relevance
“…21 In retrospect, not all women in our collective were eligible for implant-based breast reconstruction using titanium-coated polypropylene mesh (Fig. Radiotherapy, an established risk factor for postoperative complications in implantbased breast reconstruction, was also not identified as a risk factor, most likely because of the low number of patients receiving radiotherapy (two TCPM, titanium-coated polypropylene mesh; LN, lymph nodes; SSM, skin-sparing mastectomy; NSM, nipple-sparing mastectomy; NSSM, no skin-sparing mastectomy; MRM, modified radical mastectomy.…”
Section: Table 2 Overall Complications With Titanium-coated Polypropmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In retrospect, not all women in our collective were eligible for implant-based breast reconstruction using titanium-coated polypropylene mesh (Fig. Radiotherapy, an established risk factor for postoperative complications in implantbased breast reconstruction, was also not identified as a risk factor, most likely because of the low number of patients receiving radiotherapy (two TCPM, titanium-coated polypropylene mesh; LN, lymph nodes; SSM, skin-sparing mastectomy; NSM, nipple-sparing mastectomy; NSSM, no skin-sparing mastectomy; MRM, modified radical mastectomy.…”
Section: Table 2 Overall Complications With Titanium-coated Polypropmentioning
confidence: 99%
“…[4][5][6] The additional advantages of these supportive interpositional materials are based on the reduced surgical time compared with autologous tissue reconstruction. 21 However, the indications for applying acellular dermal matrix or titaniumcoated polypropylene mesh differ considerably based on the surgeon's experience, the patient's skin condition, and the approval status of the device. The limitations are associated with higher risks for implant migration, malpositioning of the inframammary fold, and poor implant coverage at the lower lateral and inferior poles.…”
mentioning
confidence: 99%
“…Reducing the number of red blood cell (RBC) transfusions may reduce nonrelapse mortality. A Swiss study in patients receiving intensive chemotherapy for hematologic malignancy and stem cell transplantation showed that a change from a double to single unit RBC transfusion policy is safe, sufficient to treat anemia, and associated with a reduction by 25% in RBC transfusion requirements and reduction in other complications associated with RBC transfusion (11). There was no evidence of more severe bleeding or more platelet transfusions during the single unit period, and the overall survival was similar in both single and double unit cohorts.…”
mentioning
confidence: 99%
“…In one study, single-unit transfusion policy was associated with decreased RBC use without increases in bleeding or platelet transfusion. 26 Another demonstrated that increasing the number of RBC units transfused was associated with an increased risk of infection. 27 The Dutch WOMB trial, in which obstetric patients with acute anemia postpartum were randomized to receive either RBC transfusion (a median of 2 RBC units) or expectant management, was unable to demonstrate noninferiority in physical fatigue at 3 days postpartum with expectant management, although the difference was small.…”
Section: Discussionmentioning
confidence: 99%